Top-down targeted network analysis of critical mineral commodities applied to international geochemistry database - Eli K. Moore; Joshua M. Rosera; Graham W. Lederer (Journal of Geochemical Exploration, 2026)

Impact of age and rurality on colorectal cancer outcomes in the United States - Caitlyn Grunert; Meng-Han Tsai; Charles R. Rogers; Sydney Howard; Rachel Hogg-Graham; Courtney Martin; Darwin Conwell; Adetunji T. Toriola; Avinash Bhakta; Justin X. Moore (Cancer Causes & Control, 2026)
Background While overall colorectal cancer (CRC) rates have declined in the United States (U.S.), early-onset CRC (EO-CRC), diagnosed before age 50, has increased. Rural U.S. residents face higher CRC incidence than non-rural counterparts. We aimed to examine the relationship between age at diagnosis and EO-CRC outcomes and whether rurality modify these associations. Methods We analyzed data from 835,907 patients aged 20–79 years in the 2006–2020 SEER Program. Rurality was defined using U.S. Department of Agriculture Rural–Urban Commuting Area (RUCA) codes. Multivariable logistic regression models were used to examine associations between age, rurality, and late-stage CRC diagnosis. Competing-risk regression models were applied to evaluate CRC-specific mortality, accounting for non–CRC deaths. Patients aged 50–59 years residing in non-rural areas served as the reference group for joint age–rurality analyses. All models adjusted for demographic, socioeconomic, clinical, and treatment factors. Results Patients aged 30–39 (aOR: 1.49, 95% CI: 1.44–1.54) and 40–49 (aOR: 1.43, 95% CI: 1.40–1.46) had significantly higher odds of late-stage CRC compared with those aged 50–59, with the strongest associations observed among non-rural patients aged 30–39 (aOR: 1.52, 95% CI: 1.46–1.58). In competing-risk models, rural patients were at higher CRC-specific mortality across all age groups, with relative hazard increases ranging from 8% in older adults (70-79) to 21% in younger adults (20-29) compared with their non-rural counterparts. Conclusion Adults aged 30–49 had higher odds of late-stage CRC than those 50–59, especially in non-rural areas. Rural residence was associated with higher CRC-specific mortality across all ages. Overall, age more strongly predicted late-stage diagnosis, while rurality more strongly predicted mortality. Earlier detection and improved clinical awareness in younger adults may reduce advanced-stage disease and CRC deaths.

Two peas in a pod: Efficacy of S-methoprene in combination with piperonyl butoxide for the control of different strains of the lesser grain borer, Rhyzopertha dominica (F.) (Coleoptera: Bostrychidae) - Maria Κ. Sakka; Graham Moores; Marina Gourgouta; Mariastela Vrontaki; Christos G. Athanassiou (Journal of Stored Products Research, 2026)

The functional effects of African lions on co-occurring carnivores differ across species pairs and with changes in resource availability and lion abundance - Kristoffer T. Everatt; Leah Andresen; Jennifer F. Moore; James E. Hines; Graham I. H. Kerley (Oecologia, 2026)
Apex carnivores are known to regulate ecosystem structure and function, including via interactions with syntopic, competitively inferior carnivores. These effects may be dependent on relative carnivore density and resource availability or productivity. We investigated the functional effect of African lions as an apex carnivore on the presence of co-occurring large carnivore species across two adjoining National Parks that contrast in relative densities of carnivores and prey. We employed two-species occupancy models from track data to test statistical interactions between lions and the other syntopic large carnivore species, while accounting for each species’ habitat selection. We further investigated the influence of anthropogenic and natural variables on these co-occurrence dynamics. Our models revealed that the occurrence of each carnivore species was best predicted by access to their own key resources. We also found significant statistical interactions between lions and cheetahs, lions and leopards, and lions and spotted hyenas in resource-rich landscapes. Finally, we found limited support for the competition exclusion hypothesis between most species, with the exception of lion-African wild dog co-occurrence patterns. Species’ co-occurrence dynamics were all influenced by resource availability, with lion-leopard and lion-cheetah co-occurrence decreasing strongly with increasing resource availability. Most species co-occurrence declined with increasing occurrence of lions. The patterns revealed by this study improves predictions of how changes in resource availability and carnivore occurrence could impact carnivore community dynamics and the functional role of apex carnivores.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Evidence of heat sensitivity in people with Parkinson’s disease - Andrew P. Hunt; Aline Souza Pagnussat; Alexander Lehn; Daniel Moore; Daniel Schweitzer; E-Liisa Laakso; Ewald Hennig; Meg E. Morris; Graham Kerr; Ian Stewart (International Journal of Biometeorology, 2024)
Examining how heat affects people with Parkinson’s disease is essential for informing clinical decision-making, safety, well-being, and healthcare planning. While there is evidence that the neuropathology associated with Parkinson’s disease affects thermoregulatory mechanisms, little attention has been given to the association of heat sensitivity to worsening symptoms and restricted daily activities in people with this progressive disease. Using a cross-sectional study design, we examined the experiences of people diagnosed with Parkinson’s disease in the heat. Two-hundred and forty-seven people completed an online survey (age: 66.0 ± 9.2 years; sex: male = 102 (41.3%), female = 145 (58.7%)), of which 195 (78.9%) reported becoming more sensitive to heat with Parkinson’s disease. Motor and nonmotor symptoms worsened with heat in 182 (73.7%) and 203 (82.2%) respondents, respectively. The most commonly reported symptoms to worsen included walking difficulties, balance impairment, stiffness, tremor, fatigue, sleep disturbances, excess sweating, difficulty concentrating, and light-headedness when standing. Concerningly, over half indicated an inability to work effectively in the heat, and nearly half reported that heat impacted their ability to perform household tasks and social activities. Overall, heat sensitivity was common in people with Parkinson’s disease and had a significant impact on symptomology, day-to-day activities and quality of life.

The energy content of meals with a similar macronutrient distribution may have a greater impact on appetite sensations than food preferences in adolescents with obesity: A secondary analysis - Halim Moore; Julie Siroux; Bruno Pereira; Maud Miguet; Alicia Fillon; Celine Dionnet; Valérie Julian; Martine Duclos; Yves Boirie; Graham Finlayson; Laurie Isacco; David Thivel (Appetite, 2023)

Constitutively Synergistic Multiagent Drug Formulations Targeting MERTK, FLT3, and BCL-2 for Treatment of AML - James M. Kelvin; Juhi Jain; Aashis Thapa; Min Qui; Lacey A. Birnbaum; Samuel G. Moore; Henry Zecca; Ryan J. Summers; Jeffrey M. Switchenko; Emma Costanza; Biaggio Uricoli; Xiaodong Wang; et al. (Pharmaceutical Research, 2023)

Cold waves in Terai region of Nepal and farmer’s perception of the effect of fog events and cold waves on agriculture - Shreemat Shrestha; Murray C. Peel; Graham A. Moore (Theoretical and Applied Climatology, 2023)
Cold waves are considered one of the important extreme weather events affecting winter crop production in the Indo-Gangetic Plain (IGP). In spite of media coverage of extreme cold events in the Terai area of Nepal (Nepal section of IGP) in recent years, few studies on this topic were found. This study investigates cold waves and their impact on agriculture during winter in the Terai region of Nepal. Historical daily maximum and minimum temperature data from six stations in the Terai (Dhangadhi, Nepalgunj, Bhairahawa, Simara, Janakpur, and Biratnagar) during 1971–2015 were analyzed to study the occurrence of cold days, cold nights, extreme cold days, extreme cold nights, cold wave days, and extreme cold wave days in the Terai. The average number of cold days per annum ranges from 15.6 to 17.9 days and the extreme cold days per annum ranges from 3.2 to 3.6 days in the Terai. Except for Nepalgunj, all the Terai stations show statistically significant increasing trends in the frequency of cold days and extreme cold days over the last four decades. Similarly, the average number of cold wave days varies from 9.2 to 13.8 per annum and the average number of extreme cold wave days varies from 1.4 to 3.8 days in the Terai region of Nepal. By comparing the co-occurrence of foggy days and cold and extreme cold wave days at Biratnagar, Simara, Bhairahawa, and Nepalgunj airport, it is also observed that most of the cold and extreme cold wave days are also foggy days. The perception of farmers regarding the effect of fog and cold wave events was explored through focus group discussions at Dhanusha and Sunsari districts of Nepal and found that the fog and cold events have significantly affected their winter crops, livestock, and their day-to-day life.

Patterns and drivers of understory macroalgal assemblage structure within subtidal kelp forests - Dan A. Smale; Graham Epstein; Esther Hughes; Andrew O. M. Mogg; Pippa J. Moore (Biodiversity and Conservation, 2020)

Dmc1 is a candidate for temperature tolerance during wheat meiosis - Tracie Draeger; Azahara C. Martin; Abdul Kader Alabdullah; Ali Pendle; María-Dolores Rey; Peter Shaw; Graham Moore (Theoretical and Applied Genetics, 2020)
Key message The meiotic recombination gene Dmc1 on wheat chromosome 5D has been identified as a candidate for the maintenance of normal chromosome synapsis and crossover at low and possibly high temperatures. Abstract We initially assessed the effects of low temperature on meiotic chromosome synapsis and crossover formation in the hexaploid wheat ( Triticum aestivum L.) variety ‘Chinese Spring’. At low temperatures, asynapsis and chromosome univalence have been observed before in Chinese Spring lines lacking the long arm of chromosome 5D (5DL), which led to the proposal that 5DL carries a gene ( Ltp1 ) that stabilises wheat chromosome pairing at low temperatures. In the current study, Chinese Spring wild type and 5DL interstitial deletion mutant plants were exposed to low temperature in a controlled environment room during a period from premeiotic interphase to early meiosis I. A 5DL deletion mutant was identified whose meiotic chromosomes exhibit extremely high levels of asynapsis and chromosome univalence at metaphase I after 7 days at 13 °C, suggesting that Ltp1 is deleted in this mutant. Immunolocalisation of the meiotic proteins ASY1 and ZYP1 on ltp1 mutants showed that low temperature results in a failure to complete synapsis at pachytene. KASP genotyping revealed that the ltp1 mutant has a 4-Mb deletion in 5DL. Of 41 genes within this deletion region, the strongest candidate for the stabilisation of chromosome pairing at low temperatures is the meiotic recombination gene Dmc1. The ltp1 mutants were subsequently treated at 30 °C for 24 h during meiosis and exhibited a reduced number of crossovers and increased univalence, though to a lesser extent than at 13 °C. We therefore renamed our ltp1 mutant ‘ ttmei1 ’ ( t emperature- t olerant mei osis 1 ) to reflect this additional loss of high temperature tolerance.

Do breast quadrants explain racial disparities in breast cancer outcomes? - Yunan Han; Justin Xavier Moore; Marvin Langston; Lindsay Fuzzell; Saira Khan; Marquita W. Lewis; Graham A. Colditz; Ying Liu (Cancer Causes & Control, 2019)

A morphologically cryptic salamander reveals additional hidden diversity: evidence for ancient genetic divergence in Webster’s salamander, Plethodon websteri - Sheena Feist; Thomas Mann; Sean Graham; Jessica Wooten; Cory Toyota; Debora Mann; Madeline Balius; Jose Polanco; Peyton Wolwehender; Je’Coiya Moore (Conservation Genetics, 2019)

Mapping hot spots of breast cancer mortality in the United States: place matters for Blacks and Hispanics - Justin Xavier Moore; Kendra J. Royston; Marvin E. Langston; Russell Griffin; Bertha Hidalgo; Henry E. Wang; Graham Colditz; Tomi Akinyemiju (Cancer Causes & Control, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Short periods of high temperature during meiosis prevent normal meiotic progression and reduce grain number in hexaploid wheat (Triticum aestivum L.) - Tracie Draeger; Graham Moore (Theoretical and Applied Genetics, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Cases of maternal cannibalism in wild bonobos (Pan paniscus) from two different field sites, Wamba and Kokolopori, Democratic Republic of the Congo - Nahoko Tokuyama; Deborah Lynn Moore; Kirsty Emma Graham; Albert Lokasola; Takeshi Furuichi (Primates, 2017)

Mapping the ‘breaker’ element of the gametocidal locus proximal to a block of sub-telomeric heterochromatin on the long arm of chromosome 4Ssh of Aegilops sharonensis - Emilie Knight; Ashleigh Binnie; Tracie Draeger; Matthew Moscou; María-Dolores Rey; Justine Sucher; Surbhi Mehra; Ian King; Graham Moore (Theoretical and Applied Genetics, 2015)

Distribution and diversity of V errucomicrobia methanotrophs in geothermal and acidic environments - Christine E. Sharp; Angela V. Smirnova; Jaime M. Graham; Matthew B. Stott; Roshan Khadka; Tim R. Moore; Stephen E. Grasby; Maria Strack; Peter F. Dunfield (Environmental Microbiology, 2014)
Summary Recently, methanotrophic members of the phylum V errucomicrobia have been described, but little is known about their distribution in nature. We surveyed methanotrophic bacteria in geothermal springs and acidic wetlands via pyrosequencing of 16 S rRNA gene amplicons. Putative methanotrophic V errucomicrobia were found in samples covering a broad temperature range (22.5–81.6° C ), but only in acidic conditions ( pH 1.8–5.0) and only in geothermal environments, not in acidic bogs or fens. Phylogenetically, three 16 S rRNA gene sequence clusters of putative methanotrophic V errucomicrobia were observed. Those detected in high‐temperature geothermal samples (44.1–81.6° C ) grouped with known thermoacidiphilic ‘ M ethylacidiphilum ’ isolates. A second group dominated in moderate‐temperature geothermal samples (22.5–40.1° C ) and a representative mesophilic methanotroph from this group was isolated (strain LP 2 A ). Genome sequencing verified that strain LP 2 A possessed particulate methane monooxygenase, but its 16 S rRNA gene sequence identity to ‘ M ethylacidiphilum infernorum ’ strain V4 was only 90.6%. A third group clustered distantly with known methanotrophic V errucomicrobia . Using pmoA ‐gene targeted quantitative polymerase chain reaction, two geothermal soil profiles showed a dominance of LP 2 A ‐like pmoA sequences in the cooler surface layers and ‘ M ethylacidiphilum'‐ like pmoA sequences in deeper, hotter layers. Based on these results, there appears to be a thermophilic group and a mesophilic group of methanotrophic V errucomicrobia . However, both were detected only in acidic geothermal environments.

Inducing chromosome pairing through premature condensation: analysis of wheat interspecific hybrids - Emilie Knight; Emma Greer; Tracie Draeger; Vera Thole; Steve Reader; Peter Shaw; Graham Moore (Functional & Integrative Genomics, 2010)

The molecular features of chromosome pairing at meiosis: the polyploid challenge using wheat as a reference - Faridoon K. Yousafzai; Nadia Al-Kaff; Graham Moore (Functional & Integrative Genomics, 2010)

Structural and functional relationship between the Ph1 locus protein 5B2 in wheat and CDK2 in mammals - Faridoon K. Yousafzai; Nadia Al-Kaff; Graham Moore (Functional & Integrative Genomics, 2010)

Development of consistently crossable wheat genotypes for alien wheat gene transfer through fine-mapping of the Kr1 locus - Isabelle Bertin; Lesley Fish; Tracie N. Foote; Emilie Knight; John Snape; Graham Moore (Theoretical and Applied Genetics, 2009)

Hinge peptide combinatorial libraries for inhilbitors of botulinum neurotoxins and saxitoxin: Deconvolution strategy - Graham J. Moore; Diana M. Moore; Samir S. Roy; Lawrence J. Hayden; Murray G. Hamilton; Nora W. C. Chan; William E. Lee (Molecular Diversity, 2006)

The Genomic Organization of Retrotransposons in Brassica oleracea - Karine Alix; Carol D. Ryder; Jay Moore; Graham J. King; J. S. (Pat) Heslop-Harrison (Plant Molecular Biology, 2005)

Control of conformation changes associated with homologue recognition during meiosis - Pilar Prieto; Graham Moore; Steve Reader (Theoretical and Applied Genetics, 2005)

Construction and analysis of a BAC library in the grass Brachypodium sylvaticum : its use as a tool to bridge the gap between rice and wheat in elucidating gene content - Simon Griffiths; Sebastien Allouis; Graham Moore; Tracie N. Foote (Functional & Integrative Genomics, 2004)

Seasonal change in foraging areas and dive depths of breeding king penguins at Heard Island - Geoffrey J. Moore; Barbara Wienecke; Graham Robertson (Polar Biology, 1999)

Estimation of the Importance of Spatially Variable Nitrogen Application and Soil Moisture Holding Capacity to Wheat Production - Graham A. Moore; J. Paul Tyndale-Biscoe (Precision Agriculture, 1999)

Food requirements of breeding king penguins at Heard Island and potential overlap with commercial fisheries - Geoffrey J. Moore; Graham Robertson; Barbara Wienecke (Polar Biology, 1998)

Design and synthesis of potent tyr(OMe)5-gonadotropin-releasing hormone (GnRH) analogues with modifications at positions 6, 9 and 10 - Maria Keramida; John M. Matsoukas; George Agelis; Dimitris Panagiotopoulos; John Cladas; Debanada Pati; Graham J. Moore; Hamid R. Habibi (International Journal of Peptide Research and Therapeutics, 1998)

Preface - Takuji Sasaki; Graham Moore (Plant Molecular Biology, 1997)

Are rice chromosomes components of a holocentric chromosome ancestor? - Graham Moore; Luis Aragón-Alcaide; Michael Roberts; Steve Reader; Terry Miller; Tracie Foote (Plant Molecular Biology, 1997)